In situ growth of MOFs on Ni(OH)2 for efficient electrocatalytic oxidation of 5-hydroxymethylfurfural. Issue 86 (13th October 2021) - Wang, Dongdong; Gong, Wanbing; Zhang, Jifang; Wang, Guozhong; Zhang, Haimin; Zhao, Huijun
Abstract : A MOF modification approach is proposed to effectively suppress the oxygen evolution reaction for the electrocatalytic oxidation of 5-hydroxymethylfurfural to 2, 5-furandicarboxylic acid with 100% yield and faradaic efficiency. Abstract : A Ni-based MOF is in situ grown onto Ni(OH)2 nanosheets to effectively suppress the oxygen evolution reaction for the efficient electrocatalytic oxidation of biomass-derived 5-hydroxymethylfurfural to 2, 5-furandicarboxylic acid with 100% yield and faradaic efficiency at 1.4 V ( vs. RHE).